40 Long ambulance response time is associated with higher incidence of cardiopulmonary resuscitation and defibrillation by dispatched citizen first-responders. (26th April 2019) - Andelius, L; Hansen, CM; Lippert, F; Karlsson, L; Torp-Pedersen, C; Gislason, GH; Folke, F
Abstract : Background: Dispatching citizen first-responders by a smartphone application (app) might increase incidence of bystander cardiopulmonary resuscitation (CPR) and defibrillation in out-of-hospital cardiac arrest (OHCA). We investigated citizen first-responder rates of CPR and defibrillation according to ambulance response time. Method: From September 1, 2017 to September 1, 2018, 23 021 citizen first-responders registered through the app. After being dispatched, citizen first-responders reported whether they performed CPR or defibrillation. Distances were calculated as straight line. Ambulance response time was defined as time from dispatch to vehicle stop. Citizen first-responder CPR and defibrillation were calculated according to ambulance response times (10 min). Results: The Emergency Dispatch Center activated the system in 837 suspected OHCAs where 51% (n=431) were confirmed as cardiac arrests eligible for inclusion. The median distance from citizen first-responder to OHCA was 628 meters (365, 902; Q1, Q3), corresponding to 5 min and 14 s citizen first-responder response time (assumed speed of 2 m/s). For ambulance response times 10 min, citizen first-responders performed CPR in 29% (n=42), 40% (n=91), and 65% (n=39) of the cases, p<0.0001, respectively. The corresponding figures for defibrillation according to ambulance response time were 8% (n=11), 16% (n=36), and 28% (n=17), p=0.0005. Citizen first-responders defibrillated at total of 15% (n=64) of all OHCAs. Conclusion: A total of 15% of all OHCA patients were defibrillated by citizen first-responders. Longer ambulance response times were associated with higher rates of citizen first-responder CPR and defibrillation. Conflict of interest: Dr. CM. Hansen, Dr. F.Folke and Dr. F.Lippert have received research grants from the Lærdal Foundation. None of the other authors reported conflict of interest. Funding: Dr. L. Andelius, Dr. L. Karlsson, Dr. CM. Hansen and Dr. F.Folke have received unrestricted funding from the Danish Foundation TrygFonden.